Pengujian Resistensi Kekeringan terhadap Beberapa Genotipe Padi Beras Merah (Oryza sativa L.) Lokal Sumatera Barat pada Fase Vegetatif - Diah Sundari Ilyani; Irfan Suliansyah; Indra Dwipa (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2017)
Several varieties of rice are cultivated in West Sumatra including red rice (Oryza sativaL.) but drought is an obstacle to its cultivation. The purpose of this study was to observe the interaction of red rice with Polyethylene glycol, to determine which genotypes of red rice are ‘drought’ tolerant in the vegetative phase and to see the effect of Polyethylene glycol on the growth of red rice. This research was conducted in the Agronomy Laboratory and Greenhouse, Faculty of Agriculture, Andalas University from October to November 2016. A Complete Random Factorial Design (10 x 2) with 3 replications was used. The first factor was the genotype of the local red rice (10 tested) and the second factor was either with or without Polyethylene glycol. Data were analyzed statistically with the F-test at the 5% level. Significant differences were further tested using Duncan's New Multiple Range Test at the 5% level. The variables observed were: plant height, the number of roots and the length of the longest root penetrating a vaseline/paraffin layer (wax layer method), plant fresh and dry weight and proline content. An interaction between red rice and Polyethylene glycol (20%) was observed. Only genotype 7 “Batu Kangkung” was tolerant to ‘drought’ in the vegetative phase and treatment with Polyethylene glycol affected plant height, length and number of roots penetrating the wax layer as well as the fresh weight of the plant.